Challenges, risks and threats to human security in the 4th Industrial Revolution - Mitrović, Ljubomir M. (NBP. Nauka, bezbednosti, policija, 2020)
The world has been gradually entering the fourth industrial revolution, where a new wave of technological advancement will bring humanity into a new era of globalisation. Global supply chains will become more efficient while reducing transport costs, which will contribute to opening new markets and drive economic growth. According to an analysis by the World Economic Forum, the fourth industrial revolution will increase the level of global income and quality of life for people around the world. However, increasing intersectionality and emerging technological trends will expose humanity to new forms of security challenges, risks and threats such as Internet fraud and data theft, cyberattacks, large-scale spontaneuos migration, climate change, etc., as stated in the 2020 Global Economic Forum's Global Risk Report.
Keywords: human security; industrial revolution 4.0; globalisation; challenges, risks and threats